Getting started with Magento - Tolinski, Scott; Safari eBooks ([Birmingham, UK?] : Packt Pub., 2013)
"Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. It's structured and paced for beginners and covers the essentials they need to get started. Beginning with the very basics of installation, this course covers everything necessary to set up a basic store, with flexible functionality. If you are interested in selling products online with the largest eCommerce platform in the world, this course is ideal for you. An understanding of HTML will come in handy for modifying content, but isn't absolutely necessary."--Resource description page.
Title from resource description page (viewed Dec. 16, 2013).
Presenter, Scott Tolinski.
Keywords: Electronic commerce -- Computer programs; Web site development; Electronic books